2021
DOI: 10.3390/nu13103576
|View full text |Cite
|
Sign up to set email alerts
|

A Hypomethylating Ketogenic Diet in Apolipoprotein E-Deficient Mice: A Pilot Study on Vascular Effects and Specific Epigenetic Changes

Abstract: Hyperhomocysteneinemia (HHcy) is common in the general population and is a risk factor for atherosclerosis by mechanisms that are still elusive. A hypomethylated status of epigenetically relevant targets may contribute to the vascular toxicity associated with HHcy. Ketogenic diets (KD) are diets with a severely restricted amount of carbohydrates that are being widely used, mainly for weight-loss purposes. However, studies associating nutritional ketosis and HHcy are lacking. This pilot study investigates the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 52 publications
0
16
0
Order By: Relevance
“…The effect of the experimental diets used in this study on the systemic methylation index, the plasma adenosylmethionine to adenosylhomocysteine ratio, has been previously evaluated in ApoE —/— mice 16,17 . A significantly decreased plasma AdoMet:AdoHcy ratio was detected in KD-fed mice but not in HF-fed mice, versus controls, thus suggesting the existence of systemic hypomethylation under nutritional ketosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The effect of the experimental diets used in this study on the systemic methylation index, the plasma adenosylmethionine to adenosylhomocysteine ratio, has been previously evaluated in ApoE —/— mice 16,17 . A significantly decreased plasma AdoMet:AdoHcy ratio was detected in KD-fed mice but not in HF-fed mice, versus controls, thus suggesting the existence of systemic hypomethylation under nutritional ketosis.…”
Section: Discussionmentioning
confidence: 99%
“…After 12 weeks, mice were euthanized by carbon dioxide inhalation and aortas were collected, as previously described in detail [16][17][18] . Briefly, aortas were perfused with 10 mL of cold phosphate saline buffer (PBS), followed by 10% neutral buffered formalin (NBF) in PBS, and were then fixed overnight in 10% NBF.…”
Section: Aorta Collection and 14t-mri Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…However, there are many different opinions on the effects of BHB on atherosclerosis. Castro et al, thought that a ketone body supplement may increase the aortic atherosclerosis burden in mice [ 53 ], and, recently, a clinical study conducted by Mu et al demonstrated that an increase in the circulation level of BHB was associated with increased coronary artery disease severity in a Chinese population. However, there are many experimental and clinical studies providing evidence that ketone bodies, especially BHB, have treatment effects for atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…As a physiological process leading to the production of ketone bodies (KBs) such as acetoacetate (AcAc), beta-hydroxybutyrate (βHB) and acetone, ketogenesis not only serves as alternative fuel source, but also activates signaling cascades that can impact cell and organ function. Although high fat diets are linked to increased AAA expansion and aortic plaque formation 19,20 , recent studies suggested that a high fat -low carbohydrate ketogenic diet, as well as exogenous ketone body supplementation, can potentially reduce tissue inflammation and ameliorate the risk of vascular injury and atheroprogression 21,22 . It is unknown whether these potential benefits are limited to atherosclerosis, or whether ketosis can have a broader impact on degenerative aortopathies such as AAA expansion and rupture.…”
Section: Introductionmentioning
confidence: 99%